Diagnostic accuracy in detecting tears in the proximal biceps tendon using standard nonenhancing shoulder MRI - Dubrow SA; Streit JJ; Shishani Y; Robbin MR; Gobezie R (Dove Medical Press, 2014)
Samuel A Dubrow,1 Jonathan J Streit,2 Yousef Shishani,2 Mark R Robbin,3 Reuben Gobezie21Department of Orthopedics, Alegent Creighton Clinic, Creighton University School of Medicine, Omaha, NE, USA; 2Department of Orthopedics, Cleveland Shoulder Institute, 3Department of Radiology, University Hospitals of Cleveland, Cleveland, OH, USABackground: There is a paucity of data in the literature evaluating the performance of noncontrast MRI in the diagnosis of partial and complete tears of the proximal portion of the long head of the biceps (LHB) tendon. The objective of this study was to evaluate the accuracy of noncontrast magnetic resonance imaging (MRI) compared to arthroscopy for the diagnosis of pathology involving the intra-articular portion of the LHB tendon.Methods: We conducted a retrospective review of 66 patients (mean age 57.8 years, range 43–70 years) who underwent shoulder arthroscopy and evaluation of the LHB tendon after having had a noncontrast MRI of the shoulder. Biceps pathology was classified by both MRI and direct arthroscopic visualization as either normal, partial tearing, or complete rupture, and arthroscopy was considered to be the gold standard. We then determined the sensitivity, specificity, and positive- and negative-predictive values of MRI for the detection of partial and complete LHB tears.Results: MRI identified 29/66 (43.9%) of patients as having a pathologic lesion of the LHB tendon (19 partial and ten complete tears) while diagnostic arthroscopy identified tears in 59/66 patients (89.4%; 50 partial and 16 complete). The sensitivity and specificity of MRI for detecting partial tearing of the LHB were 27.7% and 84.2%, respectively (positive predictive value =81.2%, negative predictive value =32.0%). The sensitivity and specificity of MRI for complete tears of the LHB were 56.3% and 98.0%, respectively (positive predictive value =90.0%, negative predictive value =87.5%).Conclusion: Standard noncontrast MRI of the shoulder is limited in detecting partial tears and complete ruptures of the intra-articular LHB tendon. Surgeons may encounter pathologic lesions of the LHB tendon during arthroscopy that are not visualized on preoperative MRI.Keywords: long head biceps tendon, biceps tendon tear, MRI detection, magnetic resonance imaging, case series